Coding Bootcamps : Building Future-Proof Skills through Rapid Skills Training - World Bank (World Bank, Washington, DC, 2017)
This report studies coding bootcamps. A new kind of rapid skills training program for the digital age. Coding bootcamps are typically short-term (three to six months), intensive and applied training courses provided by a third party that crowdsources the demand for low-skills tech talent. Coding bootcamps aim at low-entry level tech employability (for example, junior developer), providing a new tool for entry into the new world of digital jobs. This report studies the characteristics, methodologies, business models and impact of five coding bootcamps operating directly or through partners in developing countries. High employability and employment rates in low-entry tech positions (for example, junior developer, freelancer, and so on) reported by coding bootcamps suggest an untapped potential of this form of rapid tech skills training. From the case studies, there are two factors that seem to exert a major influence over employment outcomes: 1. selection criteria, and 2. extent of links with the local tech ecosystem. However, there is also criticism around bootcamp programs, which have been grounded in three key arguments: quality of programming skills, employability, and "short termism." Early evidence, which is based on a limited number of sources and mostly based on the data from bootcamp providers themselves, calls for additional, more representative, and holistic research.